Welcome back, Barbacenia rogieri!. Issue 1 (4th January 2021) - Alves, Ruy José Válka; Guimarães, Alessandra Ribeiro; Kessous, Igor Musauer; Bernardo, João Pedro; Menezes, Ana Clara da Silva de; da Silva, Nílber Gonçalves
Abstract : Barbacenia rogieri (Velloziaceae), a disjunct species rare in herbaria, is redescribed from its natural habitat in Rio de Janeiro and Espírito Santo, Brazil. B. purpurea and B. rogieri are lectotypified; an epitype and a synonym are designated for the latter. Taxonomic and conservation status comments are provided along with the first color photos from its natural habitat.